2018
DOI: 10.1111/bjso.12239
|View full text |Cite
|
Sign up to set email alerts
|

How do passion for video games and needs frustration explain time spent gaming?

Abstract: Research applying self-determination theory and the dualistic model of passion (DMP) has shown video games may satisfy basic psychological needs (i.e., competence, autonomy, and relatedness) and be identified as a passion. The DMP distinguishes between healthy or harmonious passion and problematic or obsessive passion (OP), with the latter reflecting an overreliance towards one's passion to obtain needs satisfaction. The experience of daily obstructions to needs satisfaction, or needs frustration (NF), may fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 61 publications
(98 reference statements)
3
29
0
Order By: Relevance
“…In contrast, females do not generally see videogames as an activity that satisfies their basic needs [34] but prefer videogames that involve socializing [47] and therefore are more likely to use CVGs [6,52]. Thus, being female might be a risk factor for playing mobile games excessively.…”
Section: Game-use Expectancies Game Genre Age Sex and Paymentmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, females do not generally see videogames as an activity that satisfies their basic needs [34] but prefer videogames that involve socializing [47] and therefore are more likely to use CVGs [6,52]. Thus, being female might be a risk factor for playing mobile games excessively.…”
Section: Game-use Expectancies Game Genre Age Sex and Paymentmentioning
confidence: 98%
“…In this line, research suggests that FPS players are mostly male [26,49]. In general, males report spending more time gaming than females [34,50] and show higher levels of addiction [51].…”
Section: Game-use Expectancies Game Genre Age Sex and Paymentmentioning
confidence: 99%
See 2 more Smart Citations
“…Not surprisingly, studies have demonstrated that higher frustration ( Mills, Milyavskaya, Mettler, & Heath, 2018 ) and lower fulfilment ( Weinstein, Przybylski, & Murayama, 2017 ) of basic psychological needs in daily life are risk factors to the development of IGD. These findings have prompted recommendations for further research focusing on the complicated interplay between IGD and SDT associated factors ( Mills, Milyavskaya, Mettler, Heath, & Derevensky, 2018 ).…”
Section: Introductionmentioning
confidence: 99%